Can school climate or peer preference moderate the adjustment difficulties associated with peer victimization among Chinese middle school students?. (February 2023) - Wang, Cixin; Yao, Jocelyn; Patel, Ami; Li, Beilei
Most research on peer victimization has focused on Western samples, but in recent years peer victimization in China has become more prevalent. As a result, limited information is available on how peer victimization, school climate, peer preference, and adjustment difficulties impact Chinese middle school students. This cross-sectional study explored these relations. With a sample of 734 7th and 8th-grade students (54.1% male, 45.8% female) from two middle schools in Beijing, China, findings revealed that peer victimization and peer preference predicted adjustment difficulties; however, school climate did not. Although peer preference was not a significant moderator of the association between peer victimization and adjustment difficulties, school climate significantly moderated the relation between relational peer victimization and adjustment difficulties. Limitations, future directions, and implications are further discussed.